Pengurusan Danaharta Nasional Berhad: A Case For Imposing Fiduciary Duties On The Special Administrator - Salim, Mohammad Rizal (Journal of Malaysian and Comparative Law, 1999)
As a result of the recent economic collapse - the Malaysian government has established two entities to help revitalise local financial institutions. One is Danamodal with the specific objective to recapitalise troubled financial institutons. The other entity is Pengurusan Danaharta Nasional Berhad ("Danaharta") to acquire selected non-performing loans of these financial institutions. In this paper I will focus on Danaharta.